A Young Bangladeshi Boy with Primary Ciliary Dyskinesia (Kartagener’s Syndrome): A Rare Case (Community Based Medical Journal, 2022)
Kartagener’s syndrome, an autosomal recessive inherited disorder, is a subgroup of primary ciliary dyskinesias (PCD). This genetic disorder manifests from early life which distinguishes it from acquired mucociliary disorders. Kartagener’s syndrome presents as a classical triad of situs inversus, sinusitis and bronchiectasis occurring majorly due to impaired ciliary motility. A 16 year-old boy from Fulbaria, Mymensingh with left sided consolidation for 1 month and recurrent episodes of nasal congestion and lower respiratory tract infection (LRTI) since his childhood. Clinical and imaging findings revealed left sided consolidation, chronic sinusitis, bronchiectasis, dextrocardia, and situs inversus. He was treated with orally administered antibiotics, bronchodilators, mucolytics, and chest physiotherapy. He was symptomatically better with the above therapy, and started on a long-term low-dose prophylactic antibiotic. As there is no easy, reliable non-invasive diagnostic test for Kartagener’s syndrome and the correct diagnosis is often delayed by years, it may cause chronic respiratory problems with reduced quality of life. Genetic counseling and fertility issues should be addressed once Kartagener’s syndrome is diagnosed.CBMJ 2022 January: vol. 11 no. 01 P: 56-60